Entrepreneurs’ role overload and empowering leadership: A reciprocal relationship based on conservation of resources - Wang, Wei; Zhao, Xiaorui; Zhang, Xiaomeng; Liu, Yanbin; Yuan, Ping (Frontiers in Psychology, 2023)
Introduction Role overload is not new, but its increasing prevalence in recent years calls for further research. This study considers empowering leadership as a means of resource investment and proposes that it is exerted by entrepreneurs to reduce their role overload. This study adds clarity by revealing how entrepreneurs’ role overload is mitigated via the intermediate mechanism of empowering leadership. Hypotheses are derived from conservation of resources theory. Methods Data were collected from 315 entrepreneurs in China using a three-round questionnaire survey. Results This study finds that entrepreneurs’ previous experience of role overload positively relates to their current empowering leadership behavior and their previous empowering leadership behavior negatively relates to their current role overload, which implies a mediating role of empowering leadership. Specifically, the second stage of the indirect effect of previous role overload on current role overload through empowering leadership is moderated by top management team (TMT) heterogeneity. When TMT heterogeneity is higher, the negative indirect effect is stronger. Discussion This study contributes to the idea of positive psychology and extends the scope of conservation of resources theory into the fields of entrepreneurship and leadership.